Importance of psychological factors for the recovery from a first episode of acute non-specific neck pain - a longitudinal observational study. Issue 1 (December 2016) - Wirth, Brigitte; Humphreys, B.; Peterson, Cynthia
Abstract Background The influence of psychological factors on acute neck pain is sparsely studied. In a secondary analysis of prospectively collected data, this study investigated how several psychological factors develop in the first three months of acute neck pain and how these factors influence self-perceived recovery. Methods Patients were recruited in various chiropractic practices throughout Switzerland between 2010 and 2014. The follow-up telephone interviews were conducted for all patients by research assistants in the coordinating university hospital following a standardized procedure. The population of this study consisted of 103 patients (68 female; mean age = 38.3 ± 13.8 years) with a first episode of acute (<4 weeks) neck pain. Prior to the first treatment, the patients filled in the Bournemouth Questionnaire (BQ). One week and 1 and 3 months later, they completed the BQ again along with the Patient Global Impression of Change (PGIC). The temporal development (repeated measure ANOVA) of the BQ questions 4 (anxiety), 5 (depression), 6 (fear-avoidance) and 7 (pain locus of control) as well as the influence of these scores on the PGIC were investigated (binary logistic regression analyses, receiver operating curves (ROC)). Results All psychological parameters showed significant reduction within the first month. The parameter 'anxiety' was associated with outcome at 1 and 3 months (p  = 0.013, R2  = 0.40 andp  = 0.039, R2  = 0.63, respectively). Baseline depression (p  = 0.037, R2  = 0.21), but not baseline anxiety, was a predictor for poor outcome. A high reduction in anxiety within the first month was a significant predictor for favorable outcome after 1 month (p  < 0.001; R2  = 0.57). Conclusions Psychological factors emerged from this study as relevant in the early phase of acute neck pain. Particularly persistent anxiety and depression at baseline might be risk factors for a transition to chronic pain that should be addressed in the early management of neck pain patients.